GIS based environmental decision support system for municipal landfill site selection - Ohri A.; Singh P.K. (My University, 2025)
Purpose: A GIS based environmental decision support system for municipal solid waste management under Indian socio-economic and regulatory conditions, named as EDSS-MSWI has been developed. This paper intends to report the methodology and application of the EDSS-MSWI for municipal landfill site selection taking a case study of Varanasi city (India). Design/methodology/approach: EDSS-MSWI has been developed using VB.NET and ArcGIS Engine programming tools. A set of 13 criteria are selected for primary landfill site selection. Analytical hierarchy process (AHP) has been used to give weights to different criteria. The criteria were aggregated and suitability index (S) is generated using weighted linear combination (WLC) technique in GIS environment. The suitability index (0-10) values are classified into four categories (Excluded, Less Preferable, Suitable and Best Suitable) to select the landfill site. Findings: The results indicate that there are at least four locations under the "best suitable" category where adequate land seems available for landfilling in Varanasi. It is found that GIS based multi-criteria decision analysis (MCDA) can be a powerful tool for such applications. Research limitations/implications: The weights of different criteria have been based on the opinion of three experts only. This may involve subjectivity to that extent. Aggregation of more experts' views may further refine the values of weights. Practical implications: The developed tool provides a helpful guide to solid waste management planners. Originality/value: The development of EDSS-MSWI is the first of its kind in India to consider all aspects of municipal solid waste management in a holistic way and present it in an independent software form. © Emerald Group Publishing Limited.